Transaction chopping for parallel snapshot isolation - Cerone, A; Gotsman, A; Yang, H (Springer, 2015)
Modern Internet services often achieve scalability and availability by relying on large-scale distributed databases that provide consistency models for transactions weaker than serialisability. We investigate the classical problem of transaction chopping for a promising consistency model in this class—parallel snapshot isolation (PSI), which weakens the classical snapshot isolation to allow more efficient largescale implementations. Namely, we propose a criterion for checking when a set of transactions executing on PSI can be chopped into smaller pieces without introducing new behaviours, thus improving efficiency. We find that our criterion is more permissive than the existing one for chopping serialisable transactions. To establish our criterion, we propose a novel declarative specification of PSI that does not refer to implementationlevel concepts and, thus, allows reasoning about the behaviour of PSI databases more easily. Our results contribute to building a theory of consistency models for modern large-scale databases.